Mechanical ventilators availability survey in Thai ICUs (ICU-RESOURCE I study) - Kaweesak Chittawatanarat (2018)
Objective: Mechanical ventilators (MV) have been progressing rapidly. New ventilator modes and supportive equipments have been developed. However; the MV status in Thai ICUs was not available. The objective of this report was to describe the MV supply and availability in Thai ICUs and review some important characteristics regarding of the availability of MV. Material and Method: The ICU RESOURCE I study (Mechanical ventilator part) database was used in the present study. Hospital types, MV brands and models were recorded. Statistically significant differences between and among groups were defined as p-value < 0.05. Results: A total of 2,098 MVs were included in the present study. Of these, 448 electrically independent MVs (Bird's Mark) were noted (21.35%). The remainder of 1,650 (78.65%) MVs were electrically dependent MVs (eMV). About 90 percent of eMVs were from the following seven eMV brands including Benette, Hamilton, Event, Newport, CareFusion or Bird (volume type), Drager and Servo respectively. About half of them were from the two brands of Bennette and Hamilton. Recent advanced MVs including EvitaXL, Hamilton G5, Servo-I and Epi (NAVA) were more available in academic ICUs than in nonacademic ICUs. The adult HFOV could be found only in academic ICUs in this survey. Conclusion: Bird Mark ventilators were also a high proportion of the MVs in Thai ICUs. Bennette and Hamilton were the most highly available MV in this survey. Advanced MV models were more available in academic ICUs (Thai Clinical Trial Registry: TCTR-201200005).